Social support, positive caregiving experience, and caregiver burden in informal caregivers of older adults with dementia - Marta Nemcikova; Zuzana Katreniakova; Zuzana Katreniakova; Iveta Nagyova; Iveta Nagyova (Frontiers Media S.A., 2023)
IntroductionDementia is currently one of the major causes of disability and dependency among older adults worldwide. Cognitive dysfunction, neuropsychiatric symptoms, somatic complaints, and functional impairment fundamentally affect not only a person living with dementia (PLwD), but also his/her informal caregiver(s), often resulting in a high caregiver burden. A number of variables, including the caregiver's sociodemographic characteristics, the clinical characteristics of PLwD, social support, and the caregiver's personal resources determine the caregiver's burden.ObjectivesThe aim of this study was to investigate the associations of caregiver burden in informal caregivers of PLwD with perceived social support, positive caregiving experience, and applying therapeutic communication methods.MethodsThe data were collected from September 2021 to February 2022 among 115 "PLwD-informal caregiver" dyads in the community settings in Slovakia. Measures included the Zarit Burden Interview (ZBI-12), the Oslo Social Support Scale (OSSS-3), the Positive Aspects of Caregiving Scale (PACS), and two questions on applying therapeutic communication methods-reminiscence and validation according to Naomi Feil. The Short IQCODE was used for assessing cognitive decline in PLwD. Pearson's and Spearman's correlations, t-tests, Chi-square, ANOVA, and linear multiple regression analyses were used to analyze the data (IBM SPSS 27).ResultsThe mean age of informal caregivers was 54 ± 12.4 years (81.7% of women) and the mean caregiving duration was 4.8 ± 4.8 years. The mean age of PLwD was 80.5 ± 8.3 years (73.0% of women) and their Short IQCODE mean score was 4.1 ± 1.0. Lower caregiving burden was significantly associated with higher perceived social support (β = 0.33, p < 0.01), with higher positive caregiving experience (β = 0.33, p < 0.01), and higher caregiving intensity (β = 0.24, p < 0.05) among informal caregivers of PLwD. The associations between caregiver burden and applying two therapeutic communication methods were not significant.ConclusionsImplementing psycho-social and educational public health interventions focused on strengthening social support and maintaining positive perceptions of caregiving can help reduce the increased risk of caregiver burden in informal caregivers of older adults with dementia.